2023
DOI: 10.1021/acsami.3c03446
|View full text |Cite
|
Sign up to set email alerts
|

Selenium-Doped Mesoporous Bioactive Glass Regulates Macrophage Metabolism and Polarization by Scavenging ROS and Promotes Bone Regeneration In Vivo

Abstract: Bone regeneration is complex and involves multiple cells and systems, with macrophage-mediated immune regulation being critical for the development and regulation of inflammation, angiogenesis, and osteogenesis. Biomaterials with modified physical and chemical properties (e.g., modified wettability and morphology) effectively regulate macrophage polarization. This study proposes a novel approach to macrophage-polarization induction and -metabolism regulation through selenium (Se) doping. We synthesized Se-dope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…As illustrated in Figure c, the fluorescence intensity of DCF in the group of SMLEV reached 2.9 times that of the control group. Considering that the mitochondrial membrane potential (△Ψm) was sensitive to the ROS accumulation in mitochondria, , we next detected △Ψm of CT26 cells after SeM or SMLEV treatment for 24 h by using JC-1 as indicators, which typically formed aggregates in live or undamaged cells with a relatively high △Ψm while residing as monomers in the apoptotic cells with a low △Ψm. As could be seen in Figure d,e, compared to the control group, the SMLEV group showed that the lowest proportion of aggregates reached 27.7% and the highest proportion of monomers reached 71.7%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As illustrated in Figure c, the fluorescence intensity of DCF in the group of SMLEV reached 2.9 times that of the control group. Considering that the mitochondrial membrane potential (△Ψm) was sensitive to the ROS accumulation in mitochondria, , we next detected △Ψm of CT26 cells after SeM or SMLEV treatment for 24 h by using JC-1 as indicators, which typically formed aggregates in live or undamaged cells with a relatively high △Ψm while residing as monomers in the apoptotic cells with a low △Ψm. As could be seen in Figure d,e, compared to the control group, the SMLEV group showed that the lowest proportion of aggregates reached 27.7% and the highest proportion of monomers reached 71.7%.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, excess ROS induces inflammatory cell infiltration and macrophage polarization through mitochondrial homeostasis disruption and production of pro-inflammatory factors, forming a vicious cycle of central nerve inflammation and ROS production, further aggravating inflammation and the formation of glial cell scar. In non-malignant conditions, selenium supplementation of macrophages attenuates the proinflammatory function of macrophages by switching macrophage activation from the pro-inflammatory phenotype M1 to the anti-inflammatory phenotype M2 [ 63 , 64 ]. Our results suggest that FSZ NPs exhibit the ability to regulate macrophage polarization towards the protective phenotype M2.…”
Section: Discussionmentioning
confidence: 99%